Homecomings : returning POWs and the legacies of defeat in postwar Germany - Biess, Frank 1966- (Princeton Univ. Press, 2006)
Impending defeat: military losses, the Wehrmacht and ordinary Germans -- Confronting defeat: returning POWs and the politics of victimization -- Embodied defeat: medicine, psychiatry, and the trauma of the returned POW -- Survivors of totalitarianism: returning POWs and the making of West German citizens -- Antifascist conversions: returning POWs and the making of East German citizens -- Parallel exclusions: the West German POW trials and the East German purges -- Absent presence: missing POWs and MIAs -- Divided reunion: the return of the last POWs -- Histories of the aftermath